Effect of Ag Addition on the Structural Properties of Ba0.5Sr0.5Co0.8Fe0.2O3-?–Sm0.2Ce0.8O1.9 Composite Cathode Powder - Yusop, Umira Asyikin; Abd.Rahman, Hamimah; Kang Huai, Tan (International Journal of Integrated Engineering, 2019)
Barium strontium cobalt ferrite (BSCF) materials are one of the effective cathode materials for solid-oxide fuel cells (SOFCs) because of their high conductivity and excellent catalytic activity for oxygen reduction and mobility. The ionic conductivity of this type of composite cathode can be improved by adding some catalyst materials to help enhance their electrode activity toward oxygen reduction reaction. This study aimed to investigate the effects of Argentum (Ag) as a catalyst material toward Ba0.5Sr0.5Co0.8Fe0.2O3-?–Sm0.2Ce0.8O1.9 (BSCF-SDC) composite cathode powders. The powders were mixed by using high-energy ball milling (HEBM) at 550 rpm and went through calcination process at 950 °C. Then, the calcined BSCF-SDC composite cathode powder were dry milled with Ag at five different weight percentages, start with 1wt% until 5wt%. The powders were then characterized by various analytical methods. Firstly, X-ray diffraction (XRD) was used for phase and structure identification. Secondly, Zetasizer Nano ZS was used to determine particle size. Then, the Archimedes principle to examine density and porosity also Field-Emission Scanning Electron Microscopy (FESEM) to identify the morphology of each sample. XRD results demonstrated that there was existence of impurities on BSCF-SDC and BSCF-SDC-Ag composite cathode powder after went through calcination and mixing process. This situation occurs because of the reaction of alkaline oxide with CO2 during the calcination process and can be triggered when the composite powder was mixed using HEBM method. Zetasizer results revealed that the powder particles size tends to increase with increasing amount of Ag addition and FESEM morphology also shows an enlargement on particle shape along with increasing of Ag amount.  Furthermore, the porosity (20%-40%) and density show an acceptable value as a good property needed for SOFC cathodes. All these findings indicated the effectiveness Ag addition has shown positive results on the structural properties of BSCF-SDC composite cathode powder.